Solving motion planning problems - Pereira, André Grahl (2014)
This work considers a family of motion planning problems with movable blocks. Such problem is de ned by a maze grid occupied by immovable blocks (walls) and free squares. There are k movable blocks (stones) and k fixed goal squares. The man is a movable block that can traverse free squares and move stones between them. The problem goal is to move the stones from their initial positions to the goal squares with the minimum number of stone moves. (Párrafo extraído del texto a modo de resumen)